Fiscal Consolidation and Public Wages - Chang, Juin-Jen.; Lin, Hsieh-Yu.; Susan Yang, Shu-Chun.; Traum, Nora. (Washington, D.C. : International Monetary Fund, 2019)
A New Keynesian model with government production, public compensation, and unemployment is fit to U.S. data to study the macroeconomic and fiscal effects of public wage reductions. We find that accounting for the type of government spending is crucial for its macroeconomic implications. Although reductions in public wages and government purchases of goods have similar effects on total output and the fiscal balance, the former can raise private output slightly, in contrast to the substantial contractionary effects of the latter. In addition, the baseline estimation finds that exogenous public wage reductions decrease private wages. Model counterfactuals show that sufficiently rigid nominal private wages can reverse the response of private wages, as the rigidity dampens the labor reallocation effect from the public to private sector that exerts downward pressure on private wages.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet